The need of Change in Contemporary Nepalese Foreign Policy - Dahal, Ram Kumar (Journal of Political Science, 2018)
The year 2017 has witnessed important changes in Nepal including the holding of Central, Provincial and Local elections in course of implementing the federal constitution-the constitution of Nepal, 2015. Besides these national changes, important changes have occurred in regional and global politics. In the changed national, regional and global context, Nepal has to readjust, reorient and reformulate its foreign policy to serve the growing needs and aspirations of its people. Both the internal and external issues and challenges have to be timely and properly addressed by means of an appropriate contemporary Nepalese foreign policy. The nonaligned foreign policy formulated during the cold war period has to develop new mechanisms and capabilities to cope with the changing time and situation, to fulfill the growing aspirations and expectations of the Nepalese people in the present context and to maintain its independent regional and global image and personality. In this context, Nepal has to realize the significance of its specific, unique and peculiar characteristics and convert/transform them as elements of national power and contribute towards strengthening/consolidating its foreign policy. Journal of Political Science, Volume XVIII, 2018, Page: 82-113